L'action en justice des parties prenantes dans le cadre de la Responsabilité Sociale de l'Entreprise - Lopez, Laëtitia (Université Jean Moulin Lyon 3, 2016)
L’action en justice intentée en matière de Responsabilité Sociale de l’Entreprise révèle certaines limites lorsque les justiciables parties prenantes souhaitent protéger leurs intérêts. Par une juridicisation du droit de la RSE à mi-chemin entre la soft law et la hard law, l’action en justice des parties prenantes pourrait être véritablement efficiente. Dès lors, les mécanismes processuels traditionnels sont insuffisants lorsqu’il s’agit d’agir en justice dans ce domaine. C’est notamment à travers l’intérêt et la qualité à agir en justice des parties prenantes que des aménagements de la procédure civile vont être véritablement nécessaires. Des améliorations supplémentaires telles que l’instauration d’une action de groupe élargie au domaine de la RSE et davantage américanisée permettrait notamment aux parties prenantes d’assurer leur défense grâce à un dispositif nouveau très efficace. De plus et par la voie extrajudiciaire des modes alternatifs de règlement des litiges, les acteurs de la RSE peuvent également décider de porter le différend qui les oppose hors de la connaissance du juge étatique. Ce choix d’action peut être révélateur d’une préférence pour une justice davantage négociée. Ces propositions semblent être indispensables à la mise en œuvre d’une action en justice efficace en matière de RSE. Les parties prenantes pourront alors agir en justice de manière inédite afin de parachever leur protection. Les nécessités juridiques et sociales actuelles semblent ainsi faire évoluer le droit afin que les parties prenantes puissent bénéficier d’une action en justice considérée comme un véritable contre-pouvoir face à l’entreprise.
Keywords: Action de groupe; Action en justice; Actions et défenses; Alternatives methods of settlement of disputes; CSR; CSR law's judicialization; Civil Procedure; Collective action; Conditions d'existence de l'action en justice; Corporate Social Responsibility; Droit d'agir; Intérêt à agir en justice; Juridicisation du droit de la RSE; Legal action; Legal action's conditions; Legal competency/active legitimation; Legal interest; Legal standing; M.A.R.L.; Modes alternatifs de règlement des litiges; Normes volontaires; Parties prenantes; Procédure civile; Qualité à agir en justice; RSE; Responsabilité Sociale de l'Entreprise; Responsabilité sociétale; Stakeholders; Vonluntary standards

CSR and financial performance parameters of DBBL: An empirical analysis - Farijul, Islam; Rahman, Mostafizur (International Journal of Innovation and Scientific Research, 2016)
The purpose of the current study is to show the statistical linkage between CSR expenditure of financial service firm mainly DBBL and its financial performance on the basis of some key parameters that attempts to contribute to the existing knowledge of corporate social responsibility initiatives by businesses and its ability to influence their financial performance. Consequently, the main objective is to examine the relationship between CSR and financial performance of the banking sector. For this purpose, various financial drivers are used such as EPS, DPS, NPAT, ROE, EVA ROA, MVA and, ROE and ROI. After getting all the relevant data from secondary sources like annual reports and reports from Bangladesh Bank, statistical tool like multivariate analysis in the form of Bi-variate Regression is used to depict the relationship and the developed hypotheses are tested by using Univariate analysis in the form of one sample t test under parametric test. The major finding of this study demonstrates evidence that there is a statistical significant linkage between CSR and Performance of the sample bank.
Keywords: CSR; DBBL; Financial performance parameters

Accountability of multinational corporations for human rights violations under international law - Mnyongani, Freddy (University of South Africa, 2016)
Jurisprudence
Keywords: CSR; Corporate Social Responsibility; Corporate governance; Human rights; International business enterprises; Liability for human rights violations; RSE; Social responsibility of business; Tort liability of corporations

Institutionella samspel : Om möten mellan en kommersiell och en ideell logik - Kvarnstrom, Emilia (Företagsekonomiska institutionen, Uppsala universitet, 2016)
Institutional logics create order and stability. They organize interaction and prescribe how we should behave towards each other. Such logics have generally been regarded as exclusive, in the sense that an organizational field is always guided by a single institutional logic. If there are two or more institutional logics in one setting at the same time this will create conflicting demands and contradictions. So how do organizations and individuals that act in these settings, where different institutional logics do meet, cope with the conflicting demands? This question is researched by studying actors who organize partnerships between corporations and non-profit organizations. Institutional logics have typically been studied at field level. My study follows a more recent literature strand focusing on individuals and their way of coping with conflicting institutional logics. In this thesis, interviews, text analysis and observations are used. The interviews were conducted with CSR managers of corporations, managers of corporate partners at non-profit organizations, CSR consultants, and project managers of intermediary organizations. These actors are working in an environment where conflicting institutional logics are played out. Using a narrative approach it is shown how these actors are aware of their institutional environment and its conflicts which requires them to constantly act as translators. The study shows that the actors organize an interplay between a market-logic and a social-welfare logic by bringing together the logics and establishing limits to what extent logics can be mixed. Thus, the actors can be understood as bilingual, rather than hybrids. Furthermore, it is argued that a narrative approach provides the possibility to understand institutional logics in empirical contexts as more present and visible than they are usually considered to be. The study concludes that bilingual actors balance conflicting demands and negotiate requirements set by institutional logics in their day-to-day work. Settings where institutional logics meet can hence be understood as both a contradiction and an ongoing interplay.
Keywords: Actor; Cross-sectoral partnerships; Hybrid organization; Institutional logics; Institutional theory; Narrative; Partnerships

Social legitimacy in the internal market : a dialogue of mutual responsiveness - Mulder, Jotte (European University Institute, 2016)
Social legitimacy is conventionally conceived to encompass an empirical notion based on the idea that, lacking societal acceptance, a (political or legal) regime will eventually disintegrate. This concern is reflected in the original compromise of 'embedded liberalism', which stands at the basis of the internal market of the European Union. The primary law set up of the internal market, indeed, shares the idea that the benefits of a joint commitment to free trade can only be achieved in a sustainable way if combined with an acknowledgement of domestic societal objectives within the same frameworks. Nevertheless, social legitimacy will eventually depend on the institutional design and structural rationales that embed societal values within such regimes and vice versa. This perspective is further developed, normatively, on the basis of the work of Karl Polanyi and adopted to critically assess the structural rationales that are developed within internal market adjudication, which the thesis approaches as a separate field of social ordering within the European Union. Thus, social legitimacy is developed as a requirement that perceives the legitimacy of internal market law on the basis of the extent to which it can respond and integrate social practice and values. On this point the thesis finds that the internal market lacks a sufficiently developed rationale or "common language" that is able to address the normative concerns of social legitimacy. Societal realities are often valued within a metric that risks doing violence to potentially genuine and worthwhile aspects of Member States' 'social spheres'. The thesis develops that the normative claims of social legitimacy are best addressed on the basis of a rationale of mutual responsiveness, which is considered a necessary but underdeveloped element of the constitutional form and social purpose of the internal market that is implicit in the constitutional theory of transnational effects. From a perspective of mutual responsiveness, the social purpose of the internal market is not to condition choices that necessarily require the market to trump the social sphere - or the opposite- to allow the social to necessarily trump the market. Mutual responsiveness advances a more holistic approach that conceives the market and the social, literally, as 'communicating vessels'. The normative concerns of social legitimacy and the potential of mutual responsiveness to address these normative claims are the central and connecting elements throughout the thesis.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation